PERENCANAAN PETERNAKAN SAPI POTONG DAN KAITANNYA DENGAN PEMBANGUNAN WILAYAH DI KOTA SAWAHLUNTO - Oktarifah, Dissa; Idris, Idris; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2014)
This research has purpose for (1) To know and analize the possible of beef cattle business become basic sector in being a catch with development of Sawahlunto. (2) To knowthe advisability of beef cattle business in being a catch with development of Sawahlunto. (3) To arrange the planning of expanding the straregy of beef cattle business in being a catch with develoment of Sawahlunto in 2013-2018. This kind of research is descriptif source of data is primer and scunder data. The technique of collecting data in this research is primer data that is obtaimed by direct interview of breeder that is being of research sample. While scunder data is obtaimed from organization or institution that is interalated. While data analisis that is used is analisis location quation (LQ), income multiplier and labour multiplier, analisis B/C ratio, BEP, analisis Net Present Value (NPV), analisis Internal Rate of Return (IRR) and analisis SWOT. The outcome of the research concludes that (1) From calculation product LQ is obtaimed value LQ > 1, indicate that cattle beef business in Sawahlunto is potential for being expanded, income multiplier and labour multiplier, community of RTP from beef cattle selling, selling of waste and income of manpower is the sector that is having multiple income rate RTP that give big contribute in national developing special in Sawahlunto. (2) Calculation product is obtaimed B/C ratio is 1,228, indicate that B/C ratio > 1, so according to economics is suitable for being expanded in Sawahlunto. Then if seen from IRR value is 21,006% and bigger than interes red as big as 12%. It means that economical, beef cattle business is advisability to be expanded. (3) The result of SWOT analize in expanding beef cattle business in Sawahlunto can be created strategy for expanding in :To increase the total of beef cattle population giving more illumination and following training in beef cattle business, to complete coals of controllong meet import and prospective cow and to raise knowledge and giving training program for breeder. Keywords: Beef cattle, the advisabilty of business, development Strategy.